Multifunctional MoS₂/PDA@Cu nano-composites suppress tobacco bacterial wilt via enhanced antimicrobial activity, induced resistance, and growth promotion - Mengxiao Xie; Kun Qian; Jinyan Yang; Yao Wang; Siyao Zhang; Pinlu Chen; Shili Li; Xiaoyuan Tian; Wei Ding; Juanni Chen (Pesticide Biochemistry and Physiology, 2026)

Reverse circulation mechanism in a pilot-guided reaming bit: insights from CFD-DEM simulations and an experimental study - Jine Cao; Jingchao Chen; Jinhe Bai; Hongyun Zhang; Pinlu Cao (Tunnelling and Underground Space Technology, 2025)

Comprehensive mechanistic insights into the in vitro antibiofilm activity of graphene oxide (GO) nanopesticides against phytopathogen Ralstonia solanacearum - Juanni Chen; Pinlu Chen; Mengxiao Xie; Xinyu Wei; Liang Yang; Hong Zhou; Peng Xiao; Wei Ding (Pesticide Biochemistry and Physiology, 2025)

Simulation Study of the Transport Characteristics of the Ice Core in Ice Drilling with Air Reverse Circulation - Mengke Wang; Wenbo He; Jine Cao; Bo Qi; Jingchao Chen; Pinlu Cao (Journal of Marine Science and Engineering, 2022)
Ice core drilling with air reverse circulation is a promising technology that uses high-speed airflow to transport the ice core from the bottom of the hole along the central passage of the drill pipe to the surface. Understanding how the ice core moves through the pipe is crucial for this technology in order to calculate the pneumatic parameters. In this paper, experimental study and the CFD dynamic mesh technique are used to analyze the ice core transport process and flow field characteristics. In order to prove the correctness of the dynamic mesh technique, the simulation results were verified with the experimental results, and it was found that all the simulation data were in agreement with the experimental data trend, and the maximum error was less than 10%. According to the study, once the ice core’s velocity reaches its maximum throughout the transport process, it does not change. The ice core’s maximum velocity increases with the diameter ratio and decreases with the length-to-diameter ratio, while eccentricity has no impact on the maximum velocity. When the air velocity reaches 21 m/s, the diameter ratio for the ice core with a length-to-diameter ratio of 2 increases from 0.80 to 0.92, and the maximum velocity increases from 8.92 m/s to 17.45 m/s. Data fitting demonstrates that the equation Vmax=−1.04V0 + 1.04Va describes the relationship between the ice core’s maximum velocity, Vmax, and air velocity, Va. Finally, we obtain the ice core’s suspension velocity model using CFD simulation to calculate the suspension velocity, V0.